Customer driven approach in an organizational learning: a case of information agency / Shahidatul Akhmam Rambeli and Alwi Mohd Yunus - Rambeli, Shahidatul Akhmam; Mohd Yunus, Alwi (2020)
In the era of industrial revolution 4.0, many organizations face challenges to survive in delivering product and services. Hence, there is a need for organization to equip them with knowledge and learn something new or learn from past experience in order to maintain its continuity. As such, information agency also faces a constant struggle in making their role and responsibility fully functional, easily accessible and are operating to the best of their abilities to fully aid in helping their users. This study aims is to investigate how customer driven will affect organizational learning (OL) in the information agency. OL involves individual who have to learn and those who make the shift from traditional organization to learning organizations. It specifically focuses on information professionals in information agency who play their role to ensure that they are still relevant and align with the current needs of user. The study is based on data obtained from survey questionnaires distributed to information professionals in one of the selected information agency in higher learning institution on the aspect of fulfilment of customer expectation and needs through learning in organization for their future roles. The data was analysed to evaluate and determine the relationship of customer driven needs with OL capabilities. The study suggested shared vision & mission, dialogue/communication and ICT are the main contribution on the customer driven services in information agency. It is hoped that the study can contribute to information professionals to improve their services and ensure it is still relevant and at par with the changes that take place.